Tecidos de tucumãzeiros e gentes: interações e mudanças na produção dos trançados do Arapiuns - ARANTES, Ana Carolina Vitorio (Universidade Federal do Oeste do Pará, 2023)
The newly-formed leaves of the tucumãzeiro (Astrocaryum vulgare Mart.), locally called guias, are the raw material for the production of utility objects, produced for generations in the region of the Arapiuns River, municipality of Santarém. This thesis focused on analyzing changes in the production of handicrafts, now known as Trançados do Arapiuns, and their impact on the knowledge and practices related to the tucumãzeiros and on communities landscape of the Arapiuns River. Participant observation, documents analysis, participatory mapping and semi-structured interviews were used with researchers, technicians, artisans, and other residents of the Aratapi, Vila Coroca and Vista Alegre communities, located in the Lago Grande Agroextractivist Settlement Project. From the 2000s on, intervention projects were developed in the region that culminated in a process of discovery of handicrafts, as artisans and external agents began to value them. In this trajectory, some changes in the aesthetics and production forms of this traditional handicraft have changed, as well as the way they are socially organized. The creation of the Association of Artisans of the Communities of Nova Pedreira, Vista Alegre and Coroca (AARTA) guided the continued appreciation and dissemination of this know-how and as a consequence, awards, physical stores, participation in exhibitions and declaration as municipal heritage are some materializations of the recognizing of the braids. The interests towards the tucumã trees also alternated: their leaves, for transformation into straw, became more interesting than their fruits. In practice, this interest is guided by the keen knowledge and experimentation carried out to recognize the types of tucumã, as well as the preferred tucumã individuals. Furthermore, the artisanal valorization led to the appreciation of the tucumã individuals, through the care, planting, and discarding of seeds, aiming at their presence and maintenance for later use. These practices were responsible for an increase in the amount of trees in the communities, as well as their proximity to the houses, changing the local landscape. Thus, the valorization of the braids of the Arapiuns, directly influenced by the trajectory and activities of AARTA, has brought a countless changes in the ways in which the artisans interact with each other and with the tucumãzeiros, other vegetables and the landscapes.